SEA CURRENT VELOCITY VERTICAL PROFILE STUDY ON THE SEA AROUND DERAWAN ISLANDS, EAST KALIMANTAN, INDONESIA - Hisyam Muhammad - NIM 12914019, Faisal
Standard logarithmic equation is often used to estimate the sea current velocity vertical profile curve analytically on the sea. The aim of estimating the sea current velocity vertical profile using analytic equation, which is logarithmic, is to earn u* and zo coefficient through curve fitting process that could be used as an input of a model. Although logarithmic equation is good enough to approach the current velocity vertical profile curve, but it couldn’t estimate a current velocity vertical profile under certain circumstances and location, such as outer region, therefore u* and zo coefficient which are earned will be invalid. So another equation that is believed that could approach the current velocity vertical profile for any kind of location and condition will be used. In this research basic logarithmic and parabolic equation will be used. According to the result of this research, 3 out of 4 locations on the sea around Derawan Islands are better to be approached by logarithmic equation, and only 1 location is better to be approached by parabolic equation. Parameter of good or bad of the approach of current velocity vertical profile using logarithmic or parabolic equation is based on the excellent value of compatibility, height of current velocity vertical profile that could be approached by the equation (h), and also the correlation coefficient (R) between current velocity and height above the bottom of the sea. The best sea current velocity vertical profile that could be approached by analytic equation, either it’s logarithmic or parabolic equation, is the u vertical profile in Derawan Passage with compatibility up to 97%, on the other hand, the u vertical profile in Inner Masimbung Reef is the most unsuitable current velocity vertical profile to be approached by analytic equation with compatibility only up to 66% (logarithmically) and 67% (parabolically).